Fundamentals of computer graphics - Chakraborty, Suman (Everest Publishing House, 2010)
Fundamentals of computer graphics / Chakraborty, Suman. -- Kolkata: Everest Publishing House, 2010 006.6 C426e7 7th rev ed No. of Copies : 1